IMPROVING THE REGIONAL DEVELOPMENT AND EFFICIENCY OF SMALL BUSINESS AND ENHANCING EVALUATION MECHANISMS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the importance of small business and private entrepreneurship in the regional economy, as well as the factors influencing their development and the mechanisms for evaluating their efficiency. In addition, scientific proposals and recommendations have been developed to support small businesses, increase their economic efficiency, and improve the system for evaluating their performance.